Math, asked by shaflowok, 11 months ago

(-1)×(-1)×(-1)×(-1)×(-1)is equal to​

Answers

Answered by sshakilahemad76
15

Answer:

5

Step-by-step explanation:

1+1+1+1+1= 5

in case of addition the answer of this question is 5

if you think this answer is helpful Mark me as brainlist

Answered by payalchatterje
1

Answer:

(-1)×(-1)×(-1)×(-1)×(-1) is equal to (-1).

Step-by-step explanation:

Given,(-1)×(-1)×(-1)×(-1)×(-1)

This is a problem of Algebra's simplification.

For solving this problem first we should know all operations of sign of Algebra.

I.e1.( + ) \times ( + ) = (  + )

2.( + ) \times ( - ) = ( - )

3.( - ) \times ( + ) = ( - )

4. ( - ) \times ( - ) = ( + )

Now,

( - 1) \times ( - 1) \times ( - 1) \times ( - 1) \times ( - 1) =(  + 1 )\times ( - 1) \times ( - 1) \times ( - 1) = ( - 1) \times ( - 1) \times ( - 1) = ( + 1) \times ( - 1) = ( - 1) =  - 1

After simplication value of the given term is (-1).

Some extra important formulas of Algebra,

a + b)² = a² + 2ab + b²

(a − b)² = a² − 2ab − b²

(a + b)³ = a³ + 3a²b + 3ab² + b³

(a - b)³ = a³ - 3a²b + 3ab² - b³

a³ + b³ = (a + b)³ − 3ab(a + b)

a³ - b³ = (a -b)³ + 3ab(a - b)

Similar questions